Evaluation of Interventions to Improve Ventilation in Households to Reduce Risk for Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 - Wilson Ha; Mitchell Stiefel; Jeremy Gries; Jennifer Cadnum; Maria Torres-Teran; Brigid Wilson; Curtis Donskey (Case Western Reserve University, 2022)
Background: Inadequate ventilation may contribute to the high risk for household transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).  Methods: We evaluated the effectiveness of several interventions recommended to improve ventilation in households. In 7 residential homes, carbon dioxide monitoring was conducted to assess ventilation in occupied open areas such as family rooms and in bedrooms and/or offices. Carbon dioxide levels above 800 parts per million (ppm) were considered an indicator of suboptimal ventilation for the number of people present. In 1 of the 7 homes, various interventions to improve ventilation or to filter air were assessed in a kitchen area by measuring clearance of aerosol particles produced using an aerosol-based spray system and carbon dioxide generated by cooking with a gas stove. Results: Carbon dioxide levels rose above 800 ppm in bedrooms and offices with 2 occupants when windows and doors were closed and in open areas during gatherings of 5 to 10 people; carbon dioxide levels decreased when windows or doors were opened. Clearance of carbon dioxide and aerosol particles significantly increased with interventions including running fans, operating portable air cleaners, and opening windows, particularly when there was a noticeable breeze or when a window fan was used to blow contaminated air outside.  Conclusion: In households, several measures to improve ventilation or air filtration were effective in reducing carbon dioxide accumulation or enhancing clearance of carbon dioxide and aerosol particles. Studies are needed to determine if interventions to improve ventilation can reduce the risk for airborne transmission of SARS-CoV-2 in households.